Epistimologi Politik : Studi Atas Politik Hukum Undang-Undang Perbankan No. 10/1998 - ZAINAL SAID; IRWAN ABDULLAH; LASIYO LASIYO (Universitas Muhammadiyah Yogyakarta, 2012)
Legal and political system is a subsystem in the community. Each perform a specific function to movethe social system as a whole. A rill, a national banking law norms contained in Law no. 7/1992concerning Banking as amended by Law no. 10/1998 provide less public protection arrangements(social protection) than in community settings (social deregulation). The Law. 7/1992 on banking, asamended by Law No. 10/1998 which does not restrict the ownership of commercial banks. In acompany where there are differences in ownership of company shares a number of very big difference,it will be found the majority shareholder in one hand and minority shareholders, on the other bydifferences in the number of voting rights is striking. Lessons of the past shows that the majorityprinciple causes ¬'s minority shareholders are in a position of powerlessness and disadvantage inenforcing their interests. Legal position of minority shareholders who number more weak and unableto deal with actions that harm the directors or commissioners of the company, it is caused by theposition of the majority shareholder of which is identical with the company's second organ, bothphysically and interests.